Expected Equity Option Returns - ZHANG, Xue (Institutional Knowledge at Singapore Management University, 2009)
Substantial progress has been made in investigating `Overpriced Puts Puzzle' which exists in index futures options. However, scarce studies focus on whether single-stock options also have similar problems. This thesis analyzes the returns of individual stocks' calls, puts, and their portfolios, both theoretically and empirically. Adopting the methodology of Broadie, Chernov, and Johannes (2008), I find that (1) calls have positive expected returns while puts have negative expected returns. The expected returns of both calls and puts are increasing in the strike price. (2) CAPM alphas and Sharpe ratios are reasonable for calls options, but they are too negative for OTM puts. (3) The finite sample distributions simulated by SV and SVJ models do not provide much information on the mispricing of sole calls or sole puts, while the examination of option portfolios show that only the most actively traded options exhibit similar volatility risk premiums in their straddle prices.